Global Postural Reeducation in patients with chronic nonspecific neck pain: cross-over analysis of a randomized controlled trial - Pillastrini, Paolo; Banchelli, Federico; Guccione, Andrew; Di Ciaccio, Emanuele; Violante, Francesco Saverio; Brugnettini, Monia; Vanti, Carla (La Medicina del Lavoro, 2018)
Objective: To compare the effects of Global Postural Reeducation (GPR) with Manual Therapy (MT) in participants with chronic nonspecific neck pain (NP). Methods: Pre- and post-treatment analysis of cross-over data from an RCT was done. Seventy-eight subjects with chronic nonspecific NP aged 18 to 80 years completed the trial. The group who had received GPR crossed-over to MT and the previous MT group received GPR for 9 sessions once or twice a week. Measures were assessed at pre-treatment and post-treatment. Outcome measures included pain intensity [Visual Analogue Scale (VAS)], disability (Neck Disability Index), cervical Range of Motion (ROM), and kinesiophobia [Tampa Scale of Kinesiophobia (TSK)]. Results: GPR targeted to crossed-over participants produced greater improvements in pain [Diff=-8.6; 95%CI=(-13.3; -3.8)], disability [Diff=-1.5; 95%CI=-2.8; -0.1], kinesiophobia [Diff=-1.8; 95%CI=(-3.2; -0.3)], and flexion/extension neck ROM [Diff=5.6; 95%CI=(1.8; 9.3)] at post-treatment compared to the MT group. When evaluating clinical improvement, by means of Minimal Clinically Important Differences, we found that GPR relevantly reduced neck disability with respect to MT [OR=2.13; 95% CI=(1.05; 4.35)], whereas the improvement of pain did not differ between groups [OR=1.84; 95%CI=0.85; 3.99)]. Conclusions: These results within the crossed-over group confirm previous findings from an RCT with the same sample. Sequence of treatment (GPR-to-MT vs MT-to-GPR) does not seem to weaken the greater effects of GPR compared to MT approach for chronic NP. Our findings suggest that GPR can induce hypoalgesic effects, reduce disability and kinesiophobia, and improve flexion/extension in neck ROM.